More than our pain : affect and emotion in the era of Black Lives Matter - Hinderliter, Beth, 1973-; Peraza, Steve (Albany : State University of New York Press, 2021)
"Covering rage and grief, as well as joy and fatigue, examines how Black Lives Matter activists, and the artists inspired by them, have mobilized for social justice"--
Introduction: More than our pain : affect and emotion in the era of Black Lives Matter -- Emotional work and care labor in the art and politics of Black Lives Matter / Beth Hinderliter -- The new nadir : decline and despair in U.S. race relations / Steve Peraza -- Emotion, race, and cultural trauma in #BlackLivesMatter / Erin Stephens -- Hoodrat praxis in a time of love and fury / Yomaira Figueroa and Jessica Marie Johnson -- "Heaven, for Sandra Annette Bland", "Elegy, for Tamir Rice", and The hoodie stands witness, for Trayvon Martin" / Lauren Alleyne -- "I can't breathe" : visual economies of resistance / Siona Wilson -- Stranger fruit / Jon Henry in conversation with Beth Hinderliter -- The uses of anger : Wanda Coleman's poetry of black rage and #BlackLivesMatter / Shanna Benjamin -- Bodies that matter : blackness, social symbolism, and the affective image / Derek Conrad Murray -- A eulogy in two parts and In response to the question : 'If 2017 was a poem, what would it be called?' / Dominique Christina -- Puzzle pieces on the floor : curriculum gaps, white fatigue, and misunderstanding #BlackLivesMatter / Joseph Flynn -- We're going to have to do it ourselves : banking black in the US / Andrew J. Padilla -- Black joy in the time of Ferguson / Javon Johnson.
Description based on online resource; title from digital title page (viewed on March 30, 2021).
Includes bibliographical references and index.
JSTOR
Keywords: Black lives matter movement; African Americans -- Psychology; Affect (Psychology) -- Social aspects -- United States; Affect (Psychology) -- Political aspects -- United States; Emotions -- Social aspects -- United States; Emotions -- Political aspects -- United States; African Americans -- Social conditions -- 1975-; United States -- Race relations -- Psychological aspects; Minorities -- Study and teaching; Social sciences; Electronic books; Mouvement Black Lives Matter; Noirs américains -- Psychologie; Noirs américains -- Conditions sociales -- 1975-; États-Unis -- Relations raciales -- Aspect psychologique; Minorités -- Étude et enseignement; Sciences sociales; Livres numériques.; ethnic studies; social sciences; e-books.; SOCIAL SCIENCE / Ethnic Studies / African American Studies; African Americans -- Psychology; African Americans -- Social conditions; Black lives matter movement; Emotions -- Political aspects; Emotions -- Social aspects; Race relations -- Psychological aspects; United States; Since 1975